Genome- Wide Analysis of the Nucleotide Binding Site Leucine-Rich Repeat Genes of Four Orchids Revealed Extremely Low Numbers of Disease Resistance Genes - Xue, Jia-Yu; Zhao, Tao; Liu, Yang; Liu, Yang; Zhang, Yong-Xia; Zhang, Guo-Qiang; Chen, Hongfeng; Zhou, Guang-Can; Zhang, Shou-Zhou; Shao, Zhu-Qing (Frontiers in Genetics, 2020)
Orchids are one of the most diverse flowering plant families, yet possibly maintain the smallest number of the nucleotide-binding site-leucine-rich repeat (NBS-LRR) type plant resistance (R) genes among the angiosperms. In this study, a genome-wide search in four orchid taxa identified 186 NBS-LRR genes. Furthermore, 214 NBS-LRR genes were identified from seven orchid transcriptomes. A phylogenetic analysis recovered 30 ancestral lineages (29 CNL and one RNL), far fewer than other angiosperm families. From the genetics aspect, the relatively low number of ancestral R genes is unlikely to explain the low number of R genes in orchids alone, as historical gene loss and scarce gene duplication has continuously occurred, which also contributes to the low number of R genes. Due to recent sharp expansions, Phalaenopsis equestris and Dendrobium catenatum having 52 and 115 genes, respectively, and exhibited an “early shrinking to recent expanding” evolutionary pattern, while Gastrodia elata and Apostasia shenzhenica both exhibit a “consistently shrinking” evolutionary pattern and have retained only five and 14 NBS-LRR genes, respectively. RNL genes remain in extremely low numbers with only one or two copies per genome. Notably, all of the orchid RNL genes belong to the ADR1 lineage. A separate lineage, NRG1, was entirely absent and was likely lost in the common ancestor of all monocots. All of the TNL genes were absent as well, coincident with the RNL NRG1 lineage, which supports the previously proposed notion that a potential functional association between the TNL and RNL NRG1 genes.